PLATFORMED HOPE: NAVIGATING PLATFORM MONETIZATION IN THE NIGERIAN SOCIAL MEDIA VIDEO INDUSTRY - Simon, Godwin Iretomiwa; Nieborg, David B. (AoIR Selected Papers of Internet Research, 2026)
This paper explores how creators in the Nigerian social media video industry navigate precarious labour stemming from the business models of digital platforms, specifically YouTube and Facebook. Following global developments, the economic growth and opportunities of digital platforms are creating career opportunities around the world. This has inspired Nigerian content creators who make short-form video content for millions of domestic and diaspora Africans. This paper examines the understudied precarious labour conditions of Nigerian creators in a saturated industry. Drawing from semi-structured interview with 15 workers and critical analysis of the trade press, we identify how domestic cultural norms shape the way Nigerian creators integrate spiritual beliefs in forming a sentiment of hope. This, in turn, provides inspiration to confront the precarity inherent to platform monetization. Our proposed analytical lens of “platformed hope,” identifies two faith-driven monetization strategies adopted by creators: (1) transactional para-sociality and (2) reversed labour remuneration. We contend that although hope and spirituality represent everyday practices in Nigeria, the creators’ strategies reflect practices of faith orchestrated by the unique economic, governmental, and infrastructural logics of platforms. Put differently, transactional para-sociality and reversed labour remuneration are strategic actions to attain monetization goals, but they also illustrate how Nigerian socio-cultural and economic dynamics – including the inclinations of hope and spirituality – shape platform-dependent cultural production as much as they define other aspects of life in Nigeria. Keywords: Platform labour, Nigeria, precarity, platform monetization, hope labour